Customer perception of service quality : the case of Pejabat Hal Ehwal Dalam Negeri dan Penyelidikan, Jabatan Ketua Menteri / Dayang Hafsah Abdul Naim - Abdul Naim, Dayang Hafsah (2013)
Pejabat Hal Ehwal Dalam Negeri dan Penyelidikan is an office under the Department of the Chief Minister. It is one of government body who provide service in their company performance which is one of the key functionality in enhancing their performance. The function of this organization responsible for the formulation and implementation of policies that lead to these matters in the interest of the State in particular with respect to security and public order. If PHEDN&P wants to build a good costumer perception they should provide the best service quality more effectively and efficiently on their service performance. This study on customer perception on PHEDN&P service quality aims to identify the dimensions in which the services provided by the organized PHEDPN&P to the customers and also it revels the dimensional measure and the perception of the customers further this study explores the factors that derive the perception of the customers on government service quality. The purpose of this research is to study the customer perceptions of service quality provided by PHEDN&P. The research used the service quality (SERVQUAL) dimensions. There are 5 dimensions in SERVQUAL which are reliability, responsiveness, assurance, empathy and tangible. This dimension will be used to identify customer perception towards service quality provided by PHEDN&P as quality services depend on the PHEDN&P employee's performance and their ability to provide the services. In this study, the methods used are questionnaire to identify the relevant information regarding the study on customer perception of service quality provided by PHEDN&P. The result on customer perception of service quality will suggest whether the PHEDN&P may need changes or improvement in their service performance in order to be able to provide continuously quality services.